Protection of Indigenous Legal Communities: A Critical Study of the Indigenous Legal Communities Bill - Muhammad Wildan Fauzi; Fokky Fuad (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
Recognition of indigenous legal communities in Indonesia has been constitutionally affirmed in Article 18B paragraph (2) of the 1945 Constitution of the Republic of Indonesia. However, regulations regarding the recognition and protection of indigenous legal communities are still limited, conditional, and not yet integrated into a comprehensive legal instrument. This article examines the pattern of protection of indigenous legal communities as formulated in the Draft Law on Indigenous Legal Communities and examines various weaknesses and challenges in its implementation. This research uses a normative legal method with a statutory regulatory approach and a case approach. Sources of legal materials include the Draft Law on Indigenous Legal Communities, related laws and regulations, as well as relevant legal literature and scientific articles. The results of the research indicate that this bill has a strategic role in regulating the recognition, protection, customary rights, and institutions of indigenous legal communities. However, the bill still faces several crucial issues, including the absence of a unified national institution to handle indigenous communities, the lack of a clear and equitable funding mechanism, and the potential for overlapping sectoral regulations with forestry, agrarian, and spatial planning laws. This situation has implications for legal uncertainty and the continuation of conflict and criminalization against indigenous communities. Therefore, the ratification of the Indigenous Communities Bill is needed, accompanied by institutional strengthening, a special funding scheme, and harmonization of cross-sectoral regulations to ensure the sustainable protection and empowerment of indigenous communities.